2006
DOI: 10.1007/s00701-006-0892-4
|View full text |Cite
|
Sign up to set email alerts
|

Cervical spine metastasis from adrenal pheochromocytoma

Abstract: Metastatic tumours are the most common type of tumours in the spine of which only 10% occur in the cervical spine. We report a rare presentation of metastatic pheochromocytoma of the cervical spine which was successfully treated operatively. Adequate precautions should be taken during surgery as the tumour is very vascular. Radiotherapy is useful in the treatment of residual tumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…1,22 Most studies of spinal metastases have shown a postoperative improvement in blood pressure, headaches, palpitations, and anxiety; delayed complications have usually been associated with tumor recurrence or distant metastasis. 11,13,15,33 We demonstrated that en bloc resection in one of our patients (Case 5) was associated with postoperative hypertensive cure. 12 The reasons for this are unknown but may be related to a reduction in the tumor burden and subsequent decrement in catecholamine secretion.…”
Section: Discussionmentioning
confidence: 62%
“…1,22 Most studies of spinal metastases have shown a postoperative improvement in blood pressure, headaches, palpitations, and anxiety; delayed complications have usually been associated with tumor recurrence or distant metastasis. 11,13,15,33 We demonstrated that en bloc resection in one of our patients (Case 5) was associated with postoperative hypertensive cure. 12 The reasons for this are unknown but may be related to a reduction in the tumor burden and subsequent decrement in catecholamine secretion.…”
Section: Discussionmentioning
confidence: 62%
“…The authors noted no hemodynamic changes during this procedure and detailed the safety of this approach. Kheir et al 8 reported on a patient with myelopathy who required a 2-level cervical corpectomy followed by posterolateral instrumentation and fusion. The authors described successful stabilization of the vertebrae with spinal cord decompression.…”
Section: Discussionmentioning
confidence: 99%
“…3,7,8 No reports of en bloc resection have been described. In addition, no report of postoperative hypotension with associated transient neurological decline has been reported.…”
mentioning
confidence: 99%
“…Isolated metastatic spread of pheochromocytoma to vertebral bodies is extremely rare 29 . There are only a few reports in the literature of vertebral metastases [7][8][9][10][11][12][13][14][15][16][17][18] . Our patient's presentation of an extradural thoracic pheochromocytoma is an uncommon occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The most common locations for metastasis include bone, liver, lymph node, lung 2,4,6 and spleen 7 . Although bones are the most common site for metastases, vertebral involvement is rare with only a few cases reported [7][8][9][10][11][12][13][14][15][16][17][18] . The prognosis for metastatic pheochromocytoma is poor with few cases of long term survival 2,7,19,20 .…”
Section: Introductionmentioning
confidence: 99%